2002
DOI: 10.1046/j.1464-5491.2002.00701.x
|View full text |Cite
|
Sign up to set email alerts
|

Teaching patients to monitor their risk factors retards the progression of vascular complications in high‐risk patients with Type 2 diabetes mellitus—a randomized prospective study

Abstract: Well-informed and motivated patients were more insistent to reach and maintain target values of the main risk factors of diabetic complications. The differences between the PP and SC groups were of the same order of magnitude as those between intensive and standard care groups in other studies albeit with, comparatively, a very modest cost.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
79
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(81 citation statements)
references
References 38 publications
2
79
0
Order By: Relevance
“…To prevent progression in microalbuminuric or proteinuric patients, it is important to adopt an integrated approach, comprising tight antihypertensive control, including pharmacologic blockade of the RAS by ACE inhibitors or angiotensin receptor blockers, intensified glycemic control, cessation of smoking, body weight reduction when appropriate (91), and dietary sodium restriction. As shown in Table 6, the loss of GFR was significantly less in type 2 diabetic patients receiving such integrated structured treatment in a diabetes clinic compared wth patients managed by private physicians (95)(96)(97). A recent 4-yr randomized controlled trial confirmed that changes in lifestyle can be implemented in type 2 diabetic patients with appropriate education and close follow-up (98).…”
Section: Prevention Of Progressionmentioning
confidence: 98%
“…To prevent progression in microalbuminuric or proteinuric patients, it is important to adopt an integrated approach, comprising tight antihypertensive control, including pharmacologic blockade of the RAS by ACE inhibitors or angiotensin receptor blockers, intensified glycemic control, cessation of smoking, body weight reduction when appropriate (91), and dietary sodium restriction. As shown in Table 6, the loss of GFR was significantly less in type 2 diabetic patients receiving such integrated structured treatment in a diabetes clinic compared wth patients managed by private physicians (95)(96)(97). A recent 4-yr randomized controlled trial confirmed that changes in lifestyle can be implemented in type 2 diabetic patients with appropriate education and close follow-up (98).…”
Section: Prevention Of Progressionmentioning
confidence: 98%
“…The assays were unchanged during the study period. The analytical methods were previously described (10). Renal outcome was assessed by estimated GFR (e-GFR) (11).…”
Section: Methodsmentioning
confidence: 99%
“…The extrapolation of the achievements of these programs to primary care is difficult because of both financial and organizational shortcomings. We showed previously that sharing the therapeutic responsibility with the patients themselves had a major impact on retarding the progress of microvascular complications (10). Reported herein is the second, 4-yr, phase of the study highlighting the influence of the intervention on cardiovascular outcomes.…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…Both Trento and colleagues in Italy (25) and Rachmani and colleagues in Israel, provide exemplary models of this in the published literature (26). However, to achieve improved outcomes, healthcare professionals need to create an understanding of the reality of diabetes for their patient by:…”
Section: Goal-setting and Treatment Outcomesmentioning
confidence: 99%